Design, Development, and Testing of Microplanar Coil-Based Hydrokinetic Electromagnetic-Type Energy Harvester for IoT Sensors - Iftikhar Ahmad; Maryam Abbas; Muhammad Iqbal; Ahmed M. Abdelrhman; Subramanian Chithambaram; Syed Asad Imam; Mahmood Hammad; Muneeb Ullah Anjum (Journal of Engineering)
Wireless sensor nodes (WSNs) are widely used in implementation of the new concepts such as the Internet of Things (IoT) and smart homes and societies. These WSNs use batteries as the sole power source which has numerous problems such as limited shelf life, require charging points, deep discharge, and sensitivity to temperature, and require periodic replacement and recharging. Harvesting ambient energies such as hydrokinetic, vibration, and thermal from the surrounding of WSNs provide a promising solution to the power-related problems. This research illustrates the design, development, and testing of a microplanar coil (MPC)-based hydrokinetic-based electromagnetic-type energy harvester for WSNs applications. The developed MPC-based hydrokinetic energy harvester (H-EH) utilizes the flow of water in domestic pipelines such as in the kitchen and converts it into useful electrical energy. An indigenous setup was developed to test the prototype in-lab. The H-EH produces 548 μW at a flow rate of 7 L/min at an optimum load resistance of 9 Ω. This work opens up new possibilities for developing MPC-based H-EH that can enhance the efficiency of WSNs. The research will also help to achieve self-sustained long-term operation of WSNs in advanced technologies such as IoTs, smart homes, and smart cities.